Can neuropathy be predicted by halp score in diabetic patients? - Özen Gökmuharremoğlu, Özge; Çoban Taşkın, Aysel (Acta Medica, 2025)
Objective: In the pathogenesis of diabetes mellitus, insufficient insulin secretion, improper glucose utilization, and insulin resistance in tissues lead to oxidative stress and inflammation and cause neuropathy in peripheral nerves. Hemoglobin, albumin, lymphocyte, and platelet (HALP) scores give an idea of nutritional and inflammatory status. In this report, we aimed to evaluate the relationship between HALP score and diabetic polyneuropathy. Materials and Methods: Patients admitted to our electrophysiology laboratory between 2022 and 2024 with a prediagnosis of polyneuropathy due to type 2 diabetes were included in the study. Demographic data (age, gender), hemogram (hemoglobin, lymphocyte, monocyte, platelet), biochemical values (fasting blood glucose, HbA1c, urea, creatinine, albumin, cholesterol, triglyceride), and electromyography results were retrospectively reviewed from the hospital information system. Results: The study included 155 type 2 diabetic patients with a prediagnosis of distal symmetric polyneuropathy; 79 had sensorimotor polyneuropathy, while 76 did not. Mean age was similar between groups, but males were more prevalent in the neuropathy group (p = 0.002). Cholesterol (p = 0.001) and platelet levels (p <0.001) were higher in the group without neuropathy, whereas HbA1c was higher in the neuropathy group (p = 0.03). No significant difference was observed in HALP scores between the two groups according to the presence of neuropathy (p = 0.327). Conclusion: The HALP score is known as a prognostic indicator, especially in patients with malignancy and ischemic stroke. This study found no statistically significant difference between the patient groups with diabetic polyneuropathy and those without diabetic polyneuropathy in terms of HALP scores. Comprehensive and more detailed studies are needed to investigate the potential of the HALP score to predict the development of diabetic neuropathy.